Effect of oregano essential oils on meat quality of quail - Barraza-Santos, Genesis Carolina; Hernández-Martínez, Carlos Alberto; Sinagawa-García, Sugey R.; Luna-Maldonado, Alejandro Isabel; Flores-Girón, Emmanuel; Kawas-Garza, Jorge R.; López-Puga, Jocelyn Cyan; Méndez-Zamora, Gerardo (Ecosistemas y Recursos Agropecuarios, 2021)
This study was to evaluate meat quality of quails supplemented with oregano essential oils (OEO) Lippia berlandieri Schauer (Lb) and Poliomintha longiflora Gray (Pl). Experimental diets consisted on CON: control diet, Lb: 0.20 g kg-1 Lippia berlandieri Schauer and Pl: 0.20 g kg-1 Poliomintha longiflora Gray added on diet. Variables of slaughter, physicochemicals, texture and sensorial attributes were evaluated. Lb increased (P < 0.05) slaughter weight. The pH and water holding capacity(WHC) decreased (P < 0.05) for Lb and Pl treatments, while CON treatment showed higher (P < 0.05) WHC. PI had the best value on lightness (P < 0.05).CON increased (P < 0.05) cohesiveness and resilience of meat; however, sensory atributtes did not change (P > 0.05). In conclusion, 0.20 g kg-1 of OEO in diet improved slaughter yields and meat quality.